2004
DOI: 10.1121/1.1756615
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ultrasonic scatterer size estimates for the statistical analysis and optimization of angular compounding

Abstract: Ultrasonic scatterer size estimates generally have large variances due to the inherent noise of spectral estimates used to calculate size. Compounding partially correlated size estimates associated with the same tissue, but produced with data acquired from different angles of incidence, is an effective way to reduce the variance without making dramatic sacrifices in spatial resolution. This work derives theoretical approximations for the correlation between these size estimates, and the coherence between their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…This is because compounding of uncorrelated data is most efficient. We have derived a theoretical expression for the correlation between scatterer size estimates during angular compounding [5]. Here we show more recent studies where the theoretical expressions are verified by experiments.…”
Section: Angular Compoundingmentioning
confidence: 76%
“…This is because compounding of uncorrelated data is most efficient. We have derived a theoretical expression for the correlation between scatterer size estimates during angular compounding [5]. Here we show more recent studies where the theoretical expressions are verified by experiments.…”
Section: Angular Compoundingmentioning
confidence: 76%
“…Spatial angular compounding of other parametric images of ultrasonic tissue characterization parameters such as scatterer size (Gerig et al 2004a(Gerig et al , 2004b) and attenuation coefficient estimates (Tu et al 2003) have also been shown to significantly reduce estimation noise. In addition, for elastographic applications, angular insonifications have also been utilized to image tissue displacement information in 2-D, thereby enabling estimation of both the normal and shear strain components, without assuming tissue incompressibility (Techavipoo et al 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…The methods proposed here are conceptually similar to those used in the ultrasound spatial compounding literature (Trahey et al, 1986; O’Donnell and Silverstein, 1988; Li and O’Donnell, 1994; Gerig et al, 2004a) where spatial translations or rotations of an object being imaged have been used to change the scatterer distribution, z ( x, t ), as viewed by the interrogating pulse, in an effort to sufficiently decorrelate the signal allowing independent realizations of echo signal data to be averaged. However, as an alternative approach in this study, we attempted to slightly deform the tissue to spatially redistribute these scatterers in order to obtain more independent realizations of the echo signal from a medium containing randomly positioned scatterers.…”
Section: Methodsmentioning
confidence: 99%